HUBUNGAN KESEPIAN DAN IDE BUNUH DIRI YANG DIMODERASI OLEH DEPRESI PADA REMAJA KORBAN PERCERAIAN ORANG TUA - Alia Ainunnida, Khumaira (Jurnal Ilmu Psikologi dan Kesehatan (SIKONTAN), 2022)
This study aims to determine the relationship between loneliness and suicidal ideation moderated by depression in adolescents with divorced parents. This study was conducted on 233 adolescents with divorced parents with divorce records 5 years. Collecting data in this study with the survey method. In the measurement method, the loneliness variable uses the De Jong Gierveld Loneliness Scale, BDI-II (Beck Depression Inventory-II), and Beck Scale for Suicide Ideation. The data analysis test that the writer uses in this study is a non-parametric test. This technique was chosen because of one abnormal data. The results of this study indicate that there is a relationship between loneliness and suicidal ideation in adolescents with divorced parents. In the moderating test on the depression variable, it shows that the depression variable further strengthens the relationship between loneliness and suicidal ideation.